An updated analysis of the association between CD2-associated protein gene rs9349407 polymorphism and Alzheimer’s disease in Chinese population - Gao, Shan; Hao, Jia-wei; Zhao, Ya-nan; Li, Xuan; Wang, Tao; Han, Zhi-fa; Sun, Bao-liang; Sun, Jing-yi; Liu, Gui-you (Frontiers in Neuroinformatics, 2022)
Background: Since 2011, three large-scale genome-wide association studies (GWAS) have confirmed that the CD2AP rs9349407 polymorphism is significantly connected with Alzheimer's disease (AD) in individuals of European descent. Subsequently, this association has been replicated in European populations, but is unclear whether can be replicated in Chinese. Recently, the correlation between rs9349407 and AD in Chinese population has become a research hotspot. Objective: To explore the association between rs9349407 polymorphism and AD in Chinese population. Methods: Firstly, based on the exclusion and inclusion criteria, we selected 11 independent studies of 8 articles exploring the correlation between rs9349407 variation and AD in Chinese. Secondly, we conducted meta-analysis based on fixed and random effect models and conducted heterogeneity test. Thirdly, we used additive model, dominant model, and recessive model for subgroup analysis. Results: We demonstrated that CD2AP rs9349407 polymorphism increases AD susceptibility in Chinese populations (OR = 1.33, 95% CI = 1.08–1.64, P=7.45E-03), which is consistent with the effect observed in the Caucasian. In addition, subgroup analysis showed that rs9349407 under additive model (GG+CC vs GC, OR = 0.76, 95% CI = 0.61–0.97, P=2.04E-02) and dominant model (GG+GC vs CC, OR = 0.49, 95% CI = 0.32–0.74, P=8.51E-04) were also significantly correlated with AD susceptibility, while not under recessive model. (GG vs GC+CC, OR = 0.77, 95% CI = 0.58–1.03, P=7.44E-02). Conclusion: These existing data suggest that rs9349307 is significantly correlated with the susceptibility to AD in Chinese population, but future studies with large samples are needed to confirm our findings.